Geographic disparities in physical and mental health comorbidities and socioeconomic status of residence among Medicaid beneficiaries in Utah - Horth, Roberta Z.; Bose, Srimoyee; Grafe, Carl; Forsythe, Navina; Dunn, Angela (Frontiers in Public Health, 2025)
To examine the relationship between socioeconomic deprivation and complex needs, defined as mental and physical comorbidities, we conducted a cross-sectional retrospective cohort analysis of adult Utah Medicaid beneficiaries. Our analysis included Medicaid beneficiaries with geocoded addresses aged ≥18 years in Utah (N = 157,739). We geocoded beneficiary addresses and assigned them to census block groups. We compared the socioeconomic status of block groups (Singh’s area deprivation index) with the proportion of complex needs, defined based on cluster analysis as 1 physical condition with depression or ≥ 2 physical with ≥1 mental health condition. Spatial mapping was performed of prevalence quantiles grouped by count overlaid with Medicaid-covered mental health facilities. Prevalence of complex needs was 18.9% (n = 29,742); beneficiaries with >3 emergency department visits had 12.8 odds of having complex needs; 39.7% of beneficiaries with >5,000 in annual costs had complex needs. Common comorbid conditions among beneficiaries with complex needs were hypertension (56.0%), hyperlipidemia (35.5%), depression (68.8%), anxiety (56.2%), drug use (16.0%), and alcohol use disorders (15.2%). Census block groups with higher deprivation had a higher proportion of complex needs (ρ = 0.21, p < 0.001). There was a statistically significant spatial autocorrelation of the prevalence of complex needs (Moran’s I index: 0.65; p < 0.001). Six high-count census blocks had no mental health facilities. Areas with increased socioeconomic deprivation had a greater proportion of complex needs and fewer mental health facilities. Integrated programs addressing both physical and mental health conditions with a focus on socioeconomically deprived areas might benefit Medicaid recipients in populations such as those in Utah.